Toward an Appreciation of Collective Strategy - Astley, W. Graham (Academy of Management Review, 1984)
The field of business policy has variously characterized the task of managing organization-environment relations as: (a) responding to exogenous environmental threats and opportunities, (b) negotiating resource interdepen-dencies with outside stakeholders, and (c) strategically maneuvering vis-avis competitors in industrial arenas. An alternative way of characterizing the task of managing organization-environment relations is offered. This focuses on the notion of collective strategy: the joint formulation of policy and implementation of action by the members of interorganizational collectivities.